Ensaios sobre economia do crime: controle de armas, penitenciárias e violência - Dantas, Fabiano da Costa (2021)
This thesis is composed of two independent essays related to the economics of crime. The first essay aims to investigate the effectiveness of firearm control in Brazil, through the evaluation of the Disarmament Act on firearm-related crime rates under general population, gender and youth scenarios. The methodology used comes from the synthetic control group method, which is based on the comparison of a treatment unit subjected to the intervention of interest with other counterfactual synthetic control units. The treatment unit will be Brazil, the intervention of interest will be the Disarmament Act, and the units that make up the synthetic control group consist of countries with more permissive laws on the carrying and possession of weapons than Brazil and countries in situations of armed conflict, with a time frame of 1990 to 2017. The control covariates for the estimation are based on socioeconomic and health parameters of each country, while the variables of interest are the rates of violent crimes resulting from firearms. The results indicate that the Disarmament Act was able to reduce the rates of accidents and firearm homicides among the general population, men and women, while among young people it did not show the same effectiveness in the long run. The second essay consists of investigating whether the facilities of federal prison units influence the violence rates of the municipalities where they are located. The methodology applied comes from the generalized synthetic control, which uses the union of linear models of fixed effects (Difference-in-Difference) with the synthetic control method, to estimate counterfactuals for the municipalities of Catanduvas/PR, Campo Grande/MS, Mossoró/RN, Porto Velho/RO and Brasília/DF. The variable of interest will be the municipal homicide rate, while the observed covariates consist of aspects related to violence, health and economic characteristics of the municipalities. The moment of treatment will be the year of inauguration of each prison facility and the control units consist of the Brazilian municipalities that do not have any prison facility in their territory, have the demographic density similar to the municipalities in the treatment group and that have the maximum available data consistent with the period of analysis from 1996 to 2018. The estimates point out that smaller cities with federal prison facilities are more likely to have higher homicide rates, but their confidence interval estimates were statistically insignificant, pointing to inconclusive results.